Simulated fate of catchment-derived sediment on the Great Barrier Reef shelf. (October 2018) - Margvelashvili, N.; Andrewartha, J.; Baird, M.; Herzfeld, M.; Jones, E.; Mongin, M.; Rizwi, F.; Robson, B.J.; Skerratt, J.; Wild-Allen, K.; Steven, A.
Abstract: Numerical experiments using a 3D model of fine sediment transport in the Great Barrier Reef region indicate deposition of the bulk mass of catchment sediments from river plumes within a few tens of kilometres from river mouths. A very fine fraction of easily resuspended catchment sediment has a capacity to propagate over much greater distances reaching out into the mid-shelf and outer-shelf regions. The model suggests such particles, instrumental to the development of low density flocs in the marine environment, can play a critical role in altering optical properties of water masses over the shelf during wet years. The mid-term (4 year) impact of Great Barrier Reef catchments on the probability of suspended sediment concentration exceeding the ecologically significant trigger value of 2 mg/L is confined to inshore regions adjacent to river mouth locations. Highlights: A bulk mass of catchment sediments in the GBR region deposits within a few tens of kilometres from river mouths. A very fine fraction of catchment sediment has a capacity to alter optical properties of water masses over the shelf. The impact of GBR catchments on the probability of suspended sediment exceeding 2 mg/L is confined to inshore regions.